2002
DOI: 10.1002/1521-4141(200207)32:7<2084::aid-immu2084>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

CpG motifs of bacterial DNA exacerbate colitis of dextran sulfate sodium-treated mice

Abstract: Inflammatory bowel disease (IBD) is characterized by a dysregulated intestinal immune response with elevated levels of the Th1 cytokines TNF, IL‐12 and IFN‐γ. The luminal flora has been implicated as a major factor contributing to the initiation and perpetuation of chronic intestinal inflammation by as yet unknown mechanisms. Bacterial DNA contains unmethylated cytosine‐guanosine dinucleotides (CpG) which strongly activate Th1‐mediated immune responses. To test whether these CpG‐motifs contribute to intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 36 publications
5
73
1
2
Order By: Relevance
“…Indeed, polymorphisms in TLR9 have been associated with Crohn's disease (37) and TLR9 signaling has been shown essential in mediating the anti-inflammatory effects of probiotics and CpG-ODNs in models of induced experimental colitis (38,39). On the contrary, a severe exacerbation of inflammatory disease was induced by CpG-ODN when treatment was performed after the establishment of colitis (40) and a reduced inflammatory response to bacterial sepsis has been recently observed in TLR9 Ϫ/Ϫ mice (21). An explanation for this apparent discrepancy in the control of intestinal inflammation by TLR9 is suggested by a recent study which demonstrated the expression of TLR9 on both apical and basolateral surface of intestinal epithelial cells and a different response to apical or basolateral signals: while apical stimulation of TLR9 limited inflammatory response and confers tolerance to other TLR agonists, basolateral stimulation induced inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, polymorphisms in TLR9 have been associated with Crohn's disease (37) and TLR9 signaling has been shown essential in mediating the anti-inflammatory effects of probiotics and CpG-ODNs in models of induced experimental colitis (38,39). On the contrary, a severe exacerbation of inflammatory disease was induced by CpG-ODN when treatment was performed after the establishment of colitis (40) and a reduced inflammatory response to bacterial sepsis has been recently observed in TLR9 Ϫ/Ϫ mice (21). An explanation for this apparent discrepancy in the control of intestinal inflammation by TLR9 is suggested by a recent study which demonstrated the expression of TLR9 on both apical and basolateral surface of intestinal epithelial cells and a different response to apical or basolateral signals: while apical stimulation of TLR9 limited inflammatory response and confers tolerance to other TLR agonists, basolateral stimulation induced inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Body weight was recorded daily. For therapeutic studies, mice with DSS-induced acute colitis received 100 lg of affinity-purified anti-mouse LIGHT mAbs (i.p.…”
Section: Induction and Treatment Of Colitismentioning
confidence: 99%
“…For induction of chronic colitis, BALB/c mice received four cycles of DSS treatment as described [60]. Each cycle consisted of 3% DSS in drinking water for 7 days, followed by a 10-day interval with normal drinking water.…”
Section: Induction and Treatment Of Chronic Dss-induced Colitismentioning
confidence: 99%
“…The distal third of the colon was removed and used for histological analysis as described before [60,63]. Three sections were evaluated obtained each at a 100-lm distance.…”
Section: Assessment Of Histological Scorementioning
confidence: 99%